Democratisation and Conflict in Nigeria - Iyanda Kamoru Ahmed; Adjah Ekwang Adjah (Indonesian Journal of Education and Social Sciences, 2022)
This paper discusses Democratisation And Conflict In Nigeria. The contemporary history of Nigeria is a tale of internecine conflicts and economic woes. The post-independence vision of Nigeria as a giant of Africa primed to take off into sustained development and democracy has long evaporated. Four decades of nation-building appear to have availed veiy1ittle. Rather than greater integration, there has been, across the nation, a succession of ethnic/religious conflicts, with monumental human ‘casualties and tragedies in their wake. Consequently, various views and strategies are currently being canvassed for peace and ethnic/religious conflict management in a democratic Nigeria. In a plural society like Nigeria, conflicts have been more associated with economic, religious, political, ethnic and communal issues. The surge and spate of such conflicts in Nigeria since the return of democratic dispensation, and their unprecedented spread, longevity and intensity have greatly complicated the political, social, economic and environmental problems of the country. Violent conflict threatens everything, including lives, property, development, democracy, and the viability and sustainability of our nation-state. Thus, the need to resolve conflicts in Nigeria is urgent. This chapter is, therefore, an attempt to contribute to the current debate • on civil society and ethnic/religious conflict management in a democratic Nigeria.